Peningkatan Daya Saing Produk Melalui Inovasi Produk, Branding dan Sistem Pemasaran Konsinyasi: Increasing Product Competitiveness Through Product Innovation, Branding and Consignment Marketing System - Silaningsih, Endang; Sudarijati, Sudarijati; Kartini, Tini; Hanipah, Imanda; Akhsan, Muhammad; Ningsih, Desi Fitria; Fairuz, Rozaan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Gunung Endut Village in Kalapanunggal, Sukabumi, is known as a place that often produces cassava. Cassava which is rich in carbohydrates and nutrients has become an important basic ingredient for UMKM in this village, especially for the production of cassava chips. Taking action steps carried out by the Community Service (PkM) program team from the Faculty of Economics and Business after seeing the available potential, Team PkM Djuanda University Bogor created a new product called